The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41598-020-71324-z
|View full text |Cite
|
Sign up to set email alerts
|

Novel miRNA signature for predicting the stage of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the leading causes of cancer deaths worldwide. Recently, microRNAs (miRNAs) are reported to be altered and act as potential biomarkers in various cancers. However, miRNA biomarkers for predicting the stage of HCC are limitedly discovered. Hence, we sought to identify a novel miRNA signature associated with cancer stage in HCC. We proposed a support vector machine (SVM)-based cancer stage prediction method, SVM-HCC, which uses an inheritable bi-objective combinatorial ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 55 publications
0
28
0
Order By: Relevance
“…Various machine learning methods have been developed for cancer typing and diagnosis, including subtyping of liver cancer [ 24 ], breast cancer [ 25 ], lung cancer [ 26 ], and ovarian cancer [ 27 ]. These studies have used different machine learning models, such as support vector machines (SVMs) and artificial neural networks, along with various validation methods.…”
Section: Introductionmentioning
confidence: 99%
“…Various machine learning methods have been developed for cancer typing and diagnosis, including subtyping of liver cancer [ 24 ], breast cancer [ 25 ], lung cancer [ 26 ], and ovarian cancer [ 27 ]. These studies have used different machine learning models, such as support vector machines (SVMs) and artificial neural networks, along with various validation methods.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we showed an efficient strategy to identify miRNA signatures that can stratify high risk and low risk patients as well as classify early and late tumor stages. Several computational and machine leering algorithms have been developed to explore miRNA-associated diseases [ 17 , 29 ]. Previous studies also used miRNA profiles to identify biomarkers for risk stratification [ 11 , 30 ]; however, only a few research works have been conducted to explore miRNA signatures for early tumor stage of ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Ng and Taguchi employed the tensor decomposition method to identify miRNA signature in ccRCC [ 15 ]. Previously, studies were used miRNA expression profiles of liver and breast cancer patients, followed by a support vector machine (SVM) with genetic algorithm, to predict the early and advanced stages [ 16 , 17 ]. Recently, miRNA profiles were used to detect lung cancer subtypes [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The IBCGA uses an intelligent evolutionary algorithm ( Ho et al, 2004a ), which is good at deriving an optimized SVM with feature selection. The IBCGA has been successfully applied in solving several biological problems ( Yerukala Sathipati et al, 2016 , 2019 ; Yerukala Sathipati and Ho, 2017 , 2018 , 2020 , 2021 ).…”
Section: Methodsmentioning
confidence: 99%